2019
DOI: 10.1002/jcb.29137
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases 1 and 2 inhibition suppresses cytokine production and osteoclast bone resorption in vitro

Abstract: The regulation of epigenetic factors is an emerging therapeutic target of immune function in a variety of osteolytic pathologies. Histone deacetylases (HDAC) modify core histone proteins and transcriptional processes, in addition to nonhistone protein activity. The activated immune response in rheumatoid arthritis, periodontitis, and prosthetic implant particle release stimulates the catabolic activity of osteoclasts. In this study, we investigated the effects of novel therapeutic agents targeting HDAC isozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
(168 reference statements)
2
11
0
Order By: Relevance
“…This review identified ten relevant studies analysing post-translational histone modifications implicated in chronic periodontitis, and seven relevant studies focusing on HDACi for treating periodontitis. Of these studies, there was only one cross-sectional study [ 45 ], two in vivo studies [ 46 , 47 ], and the remaining publications were in vitro [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. All publications in Table 2 and Table 3 were critically assessed to explore correlations between histone modification and the periodontal inflammatory response, along with the effects of various novel HDACi on human in vitro cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified ten relevant studies analysing post-translational histone modifications implicated in chronic periodontitis, and seven relevant studies focusing on HDACi for treating periodontitis. Of these studies, there was only one cross-sectional study [ 45 ], two in vivo studies [ 46 , 47 ], and the remaining publications were in vitro [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. All publications in Table 2 and Table 3 were critically assessed to explore correlations between histone modification and the periodontal inflammatory response, along with the effects of various novel HDACi on human in vitro cells.…”
Section: Resultsmentioning
confidence: 99%
“…In [ 48 ], significantly decreased HDAC1 and HDAC2 gene expression was observed in gingival epithelial cells and keratinocytes challenged by P. gingivalis and F. nucleatum . In monocytes stimulated by TNFα, Algate et al observed increased expression in Class I and II HDACs [ 59 ]. HDAC9 RNA expression levels appear to be significantly increased in PDL stem cells under inflammatory conditions driven by periodontitis or exposure to TNFα, which impaired osteogenic capacity in vitro [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that HDAC inhibitors can promote the proliferation of human dental pulp stem cells and the differentiation of odontoblasts (39,40). Furthermore, HDAC2 inhibition has been demonstrated to reduce cytokine production and osteoclast bone resorption (41). A previous study also reported that microRNA-22 targets HDAC6 to promote hPDLSC differentiation (42).…”
Section: Discussionmentioning
confidence: 98%
“…HDAC1 and HDAC2 belong to Class I. The inhibition of deacetylase activity of HDAC1 and HDAC2 with their selective inhibitors, BRD0302 and BRD6688, respectively, reduced cytokines and chemokines secretion from TNFα-primed monocytes and suppressed RANKL-induced TNFα-primed monocyte differentiation into osteoclasts, and the effects were more pronounced if HDAC1 and HDAC2 were collectively inhibited [111] . Thus, the demethylase ability of KDM4B and deacetylase activities of HDAC1 and HDAC2 may be useful targets to suppress periodontal tissue destruction.…”
Section: Molecular Mechanisms Of Epigenetic Alteration In Periodontitismentioning
confidence: 99%